2011
DOI: 10.1007/s00216-011-5197-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct quantification of cannabinoids and cannabinoid glucuronides in whole blood by liquid chromatography–tandem mass spectrometry

Abstract: The first method for quantifying cannabinoids and cannabinoid glucuronides in whole blood by liquid chromatography-tandem mass spectrometry (LC-MS/MS) was developed and validated. Solid-phase extraction followed protein precipitation with acetonitrile. HPLC separation was achieved in 16 min via gradient elution. Electrospray ionization was utilized for cannabinoid detection; both positive (Δ9-tetrahydrocannabinol [THC], cannabinol [CBN]) and negative (11-hydroxy-THC [11-OH-THC], 11-nor-9-carboxy-THC [THCCOOH],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
92
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 35 publications
5
92
0
Order By: Relevance
“…We quantified blood and plasma cannabinoids by a previously published LC-MS/MS method (21 ). Briefly, 0.5 mL blood or plasma was protein-precipitated with icecold acetonitrile, and supernatants were diluted and solid-phase extracted with Bond-Elut Plexa cartridges (Agilent Technologies).…”
Section: Blood and Plasma Analysismentioning
confidence: 99%
“…We quantified blood and plasma cannabinoids by a previously published LC-MS/MS method (21 ). Briefly, 0.5 mL blood or plasma was protein-precipitated with icecold acetonitrile, and supernatants were diluted and solid-phase extracted with Bond-Elut Plexa cartridges (Agilent Technologies).…”
Section: Blood and Plasma Analysismentioning
confidence: 99%
“…Numerous analytical methods for the quantification of THC and its metabolites in biological fluids have been developed, which are mostly based on gas chromatography (GC) or liquid chromatography (LC) coupled to mass spectrometry (MS) [23,24]. However, the direct and simultaneous determination of THCCOOH and its glucuronide by GC-MS is not possible as glucuronides are thermally unstable and non-volatile [25,26]. To quantify THCCOOHglucuronide by GC-MS, free THCCOOH is analyzed first and then the glucuronide is hydrolyzed to measure total THCCOOH.…”
Section: Introductionmentioning
confidence: 99%
“…The use of LC-MS/MS eliminates the need of costly and time-consuming alkaline and/ or enzymatic glucuronide hydrolysis, enabling direct measurement of free and glucuronidated THCCOOH. As native and isotopically labeled THCCOOH-glucuronide standards have become available only recently, few LC-MS/MS for quantifying THCCOOH-glucuronide in biological fluids exist [25,[29][30][31][32][33]. Schwope et al [25] and Gronewold et al [31] reported the only two existing methods for simultaneously measuring free and glucuronidated THCCOOH in whole blood, along with free and glucuronidated THC, 11-OH-THC, cannabinol and cannabidiol.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations